Randomized clinical trial of concomitant or sequential phlebectomy after endovenous laser therapy for varicose veins - Carradice, D.; Mekako, A. I.; Hatfield, J.; Chetter, I. C. (BRITISH JOURNAL OF SURGERY, 2009)
Background: The management of residual varicosities following endovenous laser therapy (EVLT) for varicose veins is contentious. Ambulatory phlebectomy may be performed concomitantly with the initial EVLT, or sequentially as a secondary procedure. This randomized trial compared these two approaches. Methods. Fifty patients with great saphenous varicose veins were randomized to EVLT alone or EVLT with concomitant ambulatory phlebectomies (EVLTAP). Principal outcomes were procedure duration, pain scores, requirement for secondary procedures and quality of life after 3 months. Results: EVLTAP took longer, but significantly decreased the requirement for subsequent interventions. There was no impairment in immediate postprocedural pain, Short Form 36 or EuroQol 5D scores with EVLTAP. Median (i.q.r.) Venous Clinical Severity Score (VCSS) at 3 months was lower for EVLTAP than for EVLT alone (0 (0-1) versus 2 (0-2); P < 0.001), with lower Aberdeen Varicose Vein Questionnaire (AVVQ) scores at 6 weeks (7.9 (4.1-10.7) vermis 13.5 (10.9-18.1); P < 0.001) and 3 months (2.0 (0.4-7.7) versus 9.6 (2.2-13.8); P = 0.015). At 1 year, there were no differences in VCSS or AVVQ scores. Conclusion: Concomitant phlebectomy with EVLT prolonged the procedure, but reduced the need for secondary procedures and significantly improved quality of life and the severity of venous disease.
Output ID 23578.
Keywords: Surgery